SOSIALISASI PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) BAGI KARYAWAN PT UNIVERSAL TEKNO REKSAJAYA KABUPATEN KUTAI TIMUR - Rindha Mareta Kusumawati; Ika Irawati (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The membership Jaminan Kesehatan Nasional (JKN) from Kutai Timur District part of Kalimantan Timur province which is the most from Pekerja Penerima Upah (PPU) – Corporate that is as much 166.290 peoples or around 45,49 % of the entire membership JKN from Kutai Timur District. BPJS Kesehatan as the organizer of JKN program have to satisfaction index target participant of JKN that is 85% which is until end of year 2018 satisfaction index of PPU-Corporate by approximately 79,9% and have to gap 5,1% to be achieved at this year. The aim of this research development is to improve satisfaction level of membership JKN through provide information to PT. Universal Tekno Reksajaya employee about rights, obligation, service flow , procedure and the rule from JKN program. The result is the employee knows legal basis of JKN program, membership segment, amount of dues/premium, service flow,benefit, call center channel and also JKN mobile application.